(3GdaUd GdSGOS aj GdHjY ef fgL GdMbs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3cGTa GdZWGAs)
(3ChdgG (B:s
(3ChdgG(B: (3GdaUd GdSGOS aj GdHjY, PgHJ GdEeGejI Edi Cfg jLH PcQ GdLfS aj GdZGFH hNGda ajg CHh MfjaI, hPgHJ Edi Cf GdeTJQj EPG QCi GdehUha Ydi GdhUas
(3BNQgG (B:s
(3BNQgG(B: (3hbGd GdTGaYj(B: (3ZPG cGf YHOjf GKfjf dCMOgeG GdKdKGf hddBNQ GdKdK acGJHGg HeFJjf Ydi GdShjI de jUM MJi jJaGhJG Ydjg GdfSHI hbO NGda GdYeheGJ aj gPg GdCMcGe GdTQYjI GdJj NGda ajgG GdLeghQ HYV ef cds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 227s
(3GdPQjYI, L (B24: 252s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis